Prevalence of metabolic syndrome and its components among adults in Gebeng, Kuantan (2012) - Phyu, Htike Myat (2013)
Background: Metabolic syndrome (MetS) is a group of risk factors associated with morbidity and mortality of non communicable disease such as Diabetes Mellitus and cardiovascular diseases. This study was conducted to measure the prevalence of MetS and its components among adults in Gebeng, Kuantan. Methods: A cross-sectional study was conducted during 2012. Houses in the villages were selected by stratified random sampling and adults between 18-59 years old in the houses were interviewed. Anthropometric measurements (weight, height, waist circumference), blood pressure, fasting blood glucose and lipid profile were taken to diagnose MetS according to Modified National Cholesterol Education Programme’s Adult Treatment Panel III (NCEP ATP III) criteria definition. Results: Out of 217 adults, prevalence of Metabolic Syndrome was 35% (95%CI: 28.89 – 41.55) and about 80% of them having at least 1 component of five factors (95% CI: 73.48 – 84.27). The prevalence of respective components are as follow: central obesity was 63.1% (95%CI: 56.56 – 69.36), elevated blood pressure was 53.5% (95%CI: 46.79 – 60.03), impaired fasting blood glucose was 24% (95% CI: 18.64 – 29.98), hypertriglyceridemia was 25.8% (95% CI: 20.32 – 31.94), low HDL cholesterol was 21.7% (95% CI: 16.56 – 27.51). Among those diagnosed with Metabolic Syndrome by modified NCEP, 75% of them were more than 40 years old, 65.8% were female, 83% were current smokers, 96% were overweight (≥ 23 kg/m2). Conclusion: Prevalence of Metabolic syndrome is as high as Malaysian nationwide survey done in 2011 and prevalence of respondents having at least 1 out 5 components was alarmingly high. It is the high time of an effective intervention program needed for this population to reduce the complications of Metabolic Syndrome including diabetes and CVD which will become epidemic in the near future.